PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATAN KETERAMPILAN PROSES SAINS SISWA - Heni Setyawati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2017)
This study aims to produce problem based learning kits which are valid, and effective to improve the science process skills. This study was a research and development (R&D). The development was made by adapting the development model by Borg and Gall consisting of seven development stages: (1) preliminary investigation, (2) planning, (3) preliminary product arrangement,(4) product validation (5) small group tryout, (6) field tryout, and (7) dissemination. The tryout subjects in this study were 40 students. The details of those students were 11 students for small group tryout, 28 students as the experimental group and the other 29 students as the control group. The experimental group was taught using problem based learning kits, while the control group using learning kits that already exist. The data were collected through product validation sheets, classroom observation sheets, students questionnaires, science process skills test and science process skills observation sheets. The results show that the developed problem based learning kits are valid and effective to improve students science process skills. The study validation showed the kits are excellent, with an average score of 4.52. The tryout results shows that the kits at the level of practicality on small groups and field are very good showing that 87.90% learning process is well done on small groups , while on the field tryout is 97.22%. The kits are effective to improve science process skills based on the comparison of the experiment and control classes. Keywords: development, science process skills, PBL kits